2014
DOI: 10.3390/ijerph110908825
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Human Buccal Cell Assay and the Pollen Abortion Assay in Assessing Genotoxicity in an Urban-Rural Gradient

Abstract: Air pollution is exacerbated near heavy traffic roads in cities. Air pollution concentration and composition vary by region and depend on urban-rural gradients. The aim of this study was to evaluate the distribution of air pollution in areas of varying population densities and to compare plant biomonitoring with an established biomarker of human exposure to traffic-related air pollution in children. The areas of study were selected near a major street in 3 different regions. Areas A, B and C represent high, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Another four works found some results related to highintensity traffic exposure, where Fleck et al (2014) used three groups to carry out their analysis, where the first two groups of children lived in cities with a high content of traffic-related air pollution and a control group living in a city with better air quality. The authors found a higher frequency of micronuclei in the exposed group.…”
Section: Study Design and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another four works found some results related to highintensity traffic exposure, where Fleck et al (2014) used three groups to carry out their analysis, where the first two groups of children lived in cities with a high content of traffic-related air pollution and a control group living in a city with better air quality. The authors found a higher frequency of micronuclei in the exposed group.…”
Section: Study Design and Main Resultsmentioning
confidence: 99%
“…The year 2021 was the most recent publication year found and 2012 the oldest. The order of countries that appeared with the most publications on the subject was Italy (Ceretti et al 2014(Ceretti et al , 2020De Donno et al 2016;Idolo et al 2018;Marcon et al 014;Panico et al 2020;Villarini et al 2018), Brazil (Alpire et al 2021;Cavalcante et al 2017;Fleck et al 2014;Silva et al 2015;Sisenando et al 2012), Malaysia (Chokeli et al 2019;Hisamuddin et al 2020;How et al 2014), Mexico (Anguiano-Vega et al 2020Gomez-Arroyo et al, 2013;López Guzmán et al 2017), Argentina (Bernardi et al 2015), and Iraq (Sabah 2021). The results of the characteristics of the included studies are shown in Table 1.…”
Section: General Characteristics Of the Included Studies And Environmental Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the use of a plant genotoxicity assay (pollen abortion assay) in conjunction with measurements of ozone concentrations may serve as an alternative for assessing regional air quality. The study, carried out by Fleck et al (15) in a city with a high demographic density, demonstrated the possible relation between high ozone concentrations and genotoxicity in plants through the pollen abortion test. In addition, this pollutant can be measured through passive monitoring, which, in addition to being a simple and less expensive apparatus, also allows to obtain a pollution gradient for the studied region.…”
Section: Introductionmentioning
confidence: 99%